The COVID - 19 pandemic’s impact on the behavioural trends in the use of printed book or e-book - Melo, Luiza Baptista (Qualitative and Quantitative Methods in Libraries; Vol 11 No 1 (2022): March issue 2022, 2022)
In a time of serious health crisis worldwide, this study is the extension of a case study already started (in February and March 2020) about the issue, reading behaviours and preferences between the use of books and e-books. The COVID-19 pandemic came to impose social distancing in the world, closing universities, schools, and other services. The implementation of Internet services has presented itself as a valid response to the change that has so brutally arisen. Naturally, everyone had to adapt to it. In this context, the question about the preferences in using books or e-books is now even more relevant. This paper analyses the impact of COVID-19 in the behavioural trends in the use of scientific information from printed books and e-books in Portugal and Brazil. To this end, a survey was conducted on a user sample from various Portuguese and Brazilian higher education schools and public libraries. The first part focused on the characterization of the respondents, which includes data on gender and qualifications attended. In the second part, we obtained viewpoints about the advantages and disadvantages of each medium, frequency of use, choice of medium according to the purpose of reading and devices used. The results let us examine the factors that influence and change the behaviours of users concerning their choice. A research such as this is beneficial to support the decision not only in selecting the information resources to be bought or pondering user preferences, but also to define strategies for advocating the use of various media that, rather than competitors, should be complimentary.